El tránsito a la dominación bizantina en Cartagena: las producciones cerámicas de la Plaza de los Tres Reyes - Méndez Ortiz, Rafael (Antigüedad y Cristianismo, 1998)
The study includes a scetch of the history and geography of Cartagena; the methodology and terminology used; a description of the history and architecture of the archeological site of the Plaza de los Tres Reyes. What is of main interest is the study of roman pottery which is described according to the different types of productions: Production A: general characteristics of production, chronology; types of fragments found at the site, all of which are believed to be of the first period. Production A/D: Problems, characteristics and chronology; a study of the only fragment found. Production C: Characteristics and an evaluation of the few fragments found. Production D: description of the history and distribution through the Empire; fragments of this type, with the predominance of the form Hayes 91. This group constitutes an important document on the history of Cartagena between the years 350 and 623. Production E and Oriental Productions "Late Roman C" and "Late Roman D". New Productions. Conclusions and graphics. (...)